The effect of drying time on the characteristics of Bandeng Sapit during storage at room temperature - Ratna Yulistiani; Sri Winarti; Erwan Adi Saputro; Fadllur Rohmawati (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Bandeng Sapit is processed milkfish that is baked and smeared with spices made using sapit. The simple processing causes the shelf life of Bandeng Sapit to be very short. The drying process is one of the solutions to increase the shelf life of Bandeng Sapit. The objective of this research was to evaluate the effect of drying time on the characteristics of milkfish during storage at room temperature..This study used a Completely Randomized Design (CRD) factorial pattern with two factors and two replications. Factor I: drying time (5 hours, 6 hours, 7 hours) and factor II : storage time (2 days, 4 days, 6 days). Data were analyzed using Analysis of Varians at 5% level and then using Duncan's Multiple Range Test (DMRT). The results showed that Bandeng Sapit with a drying time of seven hours and storage at room temperature for two days was safe and suitable for consumption, with characteristics of water content 53.21%, water activity 0.86, total microbes 5.19 CFU/gr, TBA value 1.7469 mg eq/kg, TVB-N 4.6267 mg/100gr, texture 4.6267 mm/10sec/50gr.